POLYSEMY AND FUNCTIONING OF THE INTERROGATIVE STRUCTURES IN M. SHOLOKHOV’S WORKS (Proceedings of Southern Federal University. Philology, 2012)
Gavrilova G.F.Keywords: connotation, opposite meaning, figurative meaning, semantic structure, polysemy, stylistic effect, context.The article is devoted to the polysemy and polyfunctioning of interrogative sentences in M. Sholokhov’s works. Special attention is given to the stylistic peculiarities of interrogative questions in dialogues. The article touches upon the questions of textual and subtextual semantics, connotation, introductory words and particles.